The Role of Organizations and Student Loyalty to The Development of Student Potential Management Study Program Class of 2022 at STIE Yapan - Alisman Halawa; Rifki Suwaji (Jurnal Informasi dan Teknologi, 2024)
The role of student organizations and student loyalty is very important to develop student potential both in terms of hard skills and soft skills. The purpose of this study was to determine the relationship between the role of student organizations and student loyalty to the development of student potential. The number of samples used in the study were 50 students of the Class of 2022 or semester 4 of the management study program, STIE YAPAN. This research uses quantitative methods. The results showed that the organizational role variable had a positive and significant effect on potential development at 0.001 < 0.05. The student loyalty variable has a positive and insignificant effect on potential development at 0.257 > 0.05. Organizational role variables and student loyalty simultaneously have a positive and significant effect on the development of student potential. The results of R Square show that the variable role of student organizations and student loyalty to the development of student potential is 63.8%, which means that the two independent variables are able to contribute to the potential development variable, while the remaining 36.2% is influenced by other variables outside the variables used in the study.